The Development of Library Research Topics in Indonesia During a Decade (2014-2024) on the Scopus Database: Bibliometric Analysis with Vos Viewer - Miftha Khulzannah; Hilda Syafaini Harefa; Ahmad Zukhri Siregar (Sean Institute, 2025)
The landscape of library research in Indonesia has undergone significant changes over the past decade, shifting from traditional library practices to embracing digital libraries and modern technologies. This evolution is driven by the need to adapt to technological advancements and the growing demand for digital literacy. The study aims to analyze the development of library research topics in Indonesia from 2004 to 2024, focusing on the integration of artificial intelligence (AI), machine learning, and systematic reviews, particularly in response to the COVID-19 pandemic. Utilizing bibliometric analysis through the Scopus database and VOSviewer software, the research investigates trends, collaborations, and emerging areas in library research. This approach provides a comprehensive view of the evolving research landscape. The findings reveal a pronounced shift towards digital libraries and the incorporation of modern technologies. The study highlights the role of social media as a connector between traditional library services and technological innovations, enhancing user engagement. Future directions emphasize promoting interdisciplinary collaborations and increasing digital literacy among library users.